The Role of Job Demands on Burnout with Resilience as a Moderator in Headhunters - Dharmawan, Stephanus Raymond; Zamralita (International Journal of Science and Society, 2025)
Headhunters face high job demands, increasing the risk of burnout due to prolonged work-related stress. Job demand includes physical, emotional, and cognitive efforts, while burnout is a psychological condition resulting from chronic workplace stress. Resilience refers to an individual’s capacity to cope with stress while maintaining normal functioning. This study explores the relationship between job demand and burnout among headhunters and examines the moderating role of resilience. This is a quantitative survey approach was used with 154 headhunters from recruitment companies in Jakarta with at least one year of experience. Convenience sampling was applied, and data were collected using adapted versions of the Burnout Assessment Tool, the Job Demands-Resources Questionnaire, and the Connor-Davidson Resilience Scale. The result is Job demand significantly and positively affects burnout among headhunters. Resilience moderates this relationship, with a moderation effect of 0.0150 (p < 0.001). Conclusion: Higher resilience levels help mitigate the negative impact of job demand on burnout. Recruitment companies should develop interventions to enhance resilience, reducing burnout risk and improving productivity.